Case report: Clinical and molecular features of renal gastrointestinal tumor - Makker, Simran; Rammal, Rayan; Gu, Ping; Dalbagni, Guido; Al-Ahmadie, Hikmat; Agaram, Narasimhan P.; Iyer, Gopa; Kotecha, Ritesh R. (Frontiers in Oncology, 2025)
While gastrointestinal stromal tumors (GISTs) often arise within the GI tract, it is well known that GISTs may also rarely emanate outside of the digestive system. Prior case reports have documented various primary sites in non-GI organs [extra-intestinal GIST (EGIST)], yet only one report has described a localized GIST of renal origin. Here, we describe a patient who presented with bilateral renal masses who was found to have a large unresectable renal GIST tumor treated with imatinib. We discuss treatment experience and response with systemic therapy and describe molecular data to contextualize this ultra-rare presentation within the landscape of EGIST tumors.